Colonization and the Wampanoag story - Coombs, Linda (Race to the truth., 2023)
"Until now, you've only heard one side of the story: the "discovery" of America told by Christopher Columbus, the Pilgrims, and the Colonists. Here's the true story of America from the Indigenous perspective. When you think about the beginning of the American story, what comes to mind? Three ships in 1492, or perhaps buckled hats and shoes stepping off of the Mayflower, ready to start a new country. But the truth is, Christopher Columbus, the Pilgrims, and the Colonists didn't arrive to a vast, empty land ready to be developed. They arrived to find people and communities living in harmony with the land they had inhabited for thousands of years, and they quickly disrupted everything they saw. From its "discovery" by Europeans to the first Thanksgiving, the story of America's earliest days has been carefully misrepresented. Told from the perspective of the New England Indigenous Nations that these outsiders found when they arrived, this is the true story of how America as we know it today began." --